Exploring the Effectiveness of Experience-Based Learning Approaches in Supporting Long-Term Strengthening of Character Education in Schools - Setiyatna, Hery; Mahmud, Nurhani; Astutik, Yuli; Muhkam, Mirwan Fikri (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the effectiveness of experience-based learning in strengthening sustainable character education in high schools. Using a mixed methods design combining a quasi-experimental pretest–posttest and qualitative case study, 200 students from two Indonesian schools were divided into experimental and control groups. Quantitative data were analyzed using mean difference tests and ANCOVA, while qualitative insights were obtained through interviews, observations, and reflections. The results show a significant improvement in discipline, responsibility, empathy, and cooperation among students in the experimental group. The study concludes that direct learning experiences, supported by reflection and social engagement, effectively foster long-term character values and contribute conceptually to sustainability-oriented education strategies, offering practical guidance for schools in designing experiential curricula.